Resident foreign patients receive adequate dialysis but fewer preemptive transplantations: data from the Italian pediatric dialysis registry. - Paglialonga, Fabio; Consolo, Silvia; Vidal, Enrico; Parolin, Mattia; Minale, Bruno; Giordano, Mario; Guzzo, Isabella; Benevenuta, Chiara; Roperto, Rosa; Corrado, Ciro; Mencarelli, Francesca; Chimenz, Roberto; et al. (Pediatric Nephrology, 2021)
Background: Sociocultural issues play a key role in children needing kidney replacement therapy (KRT). Methods: Data of incident patients < 18 years treated with chronic dialysis or preemptive kidney transplantation (pTx) between 2007 and 2016 were retrospectively collected from the Italian Pediatric Dialysis Registry; KRT modality and outcome were compared between patients with at least one non-Italian parent ("resident foreign patients," RFPs) and those from native parents ("domestic patients," DPs) and between the quinquennium 2007–2011 (period 1) and 2012–2016 (period 2). Results: We included 448 children (26.8% RFPs). The percentage of RFPs increased from 23 to 30.3% (p = 0.08) from periods 1 to 2. They were younger (6.7 vs. 9.4 years, p = 0.025) and less often treated with pTx (3.3 vs. 13.4%, p = 0.009) than DPs. The percentage of pTx increased from period 1 to 2 in RFPs only (8.4–18.6%, p = 0.006). Independent predictors of a lower probability of pTx were lower age, belonging to RFPs group, starting KRT in period 1 and focal segmental glomerulosclerosis or glomerulopathy as primary kidney disease. Peritoneal dialysis was the preferred dialysis modality in both groups. Age, primary kidney disease, and center size were independently associated with dialysis modality choice. Patient survival, waiting time to Tx, and dialysis modality survival were not different between the two groups. Conclusions: The proportion of patients receiving KRT born from immigrant families increased in recent years in Italy. They were younger and less often treated with pTx than domestic patients. In case of dialysis, the outcome was not different between the two groups.